Inhibition of Sphingosine-1-Phosphate Receptor 2 Prevents Thoracic Aortic Dissection and Rupture - Pan, Guangwei; Liao, Mengyang; Dai, Yong; Li, Yang; Yan, Xiaole; Mai, Wuqian; Liu, Jinping; Liao, Yuhua; Qiu, Zhihua; Zhou, Zihua (Frontiers in Cardiovascular Medicine, 2021)
ABSTRACT Background: Numerous evidences have indicated that thoracic aortic dissection (TAD) is an inflammatory disease. Sphingosine-1-phosphate receptor 2 (S1PR2) signaling is a driver in multiple inflammatory diseases. Here, we examined the S1PR2 expression in TAD lesions, and explored the effect of interfering with S1PR2 on TAD formation and progression. Methods: Aorta specimens and blood samples were collected from TAD patients and matched controls. The expression of S1PR1 and S1PR2 were examined. The effect of inhibiting S1PR2 on TAD was evaluated in a TAD mouse model induced by β-aminopropionitrile fumarate (BAPN) and AngII. The presence of sphingosine kinase 1 (SPHK1), S1P, and neutrophil extracellular traps (NETs) were investigated. Further, the association between S1PR2 signaling and NETs in TAD was analyzed. Results: In the TAD patients and mouse model, S1PR2 expression was significantly up-regulated. In the mouse model of TAD, JTE013, a specific S1PR2 antagonist, not only blunted TAD formation, and prevented aortic rupture, but also preserved elastic fiber architecture, reduced smooth muscle cells apoptosis level, and mitigated aortic wall inflammation. Augmented tissue protein expression of SPHK1, citrullinated histone H3 (CitH3, a specific marker of NETs), and serum S1P, CitH3 were detected in TAD patients. Surgical repair normalized the serum S1P and CitH3 levels. Immunofluorescence staining revealed that S1PR2 colocalized with NETs. The protein expression levels of SPHK1 and serum S1P levels positively correlated with protein expression and serum levels of CitH3, separately. While, JTE013 treatment diminished NETs formation and inappropriate NETs-derived macrophage inflammation. Conclusion: Inhibiting S1PR2 attenuates TAD formation and prevents aortic rupture. Targeting S1PR2 may provide a promising treatment strategy against TAD.